2017
DOI: 10.1242/dev.145789
|View full text |Cite
|
Sign up to set email alerts
|

Genomic integration of Wnt/β-catenin and BMP/Smad1 signaling coordinates foregut and hindgut transcriptional programs

Abstract: Digestive system development is orchestrated by combinatorial signaling interactions between endoderm and mesoderm, but how these signals are interpreted in the genome is poorly understood. Here we identified the transcriptomes of Xenopus foregut and hindgut progenitors, which are conserved with mammals. Using RNA-seq and ChIP-seq we show that BMP/Smad1 regulates dorsal-ventral gene expression in both the endoderm and mesoderm, whereas Wnt/β-catenin acts as a genome-wide toggle between foregut and hindgut prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 63 publications
0
64
0
Order By: Relevance
“…A common core of Wnt-regulated gene expression changes are more robust in orthotopic xenografts. To determine whether the gene expression changes seen in the HPAF-II pancreatic cancer were generalizable to other Wnt-addicted cancers, we compared our data to our previously published data set of a Wnt-addicted jci.org Volume 128 Number 12 December 2018 (31). The promoters of genes in the most rapidly responding clusters (i.e., C9, C10, C20, C24, and C25; TI 50 < 20 hours) were rather significantly enriched for canonical E-box motifs, bound by transcription factors, including MYC, HEY1, CLOCK, and ID2 ( Figure 4A).…”
Section: Resultsmentioning
confidence: 99%
“…A common core of Wnt-regulated gene expression changes are more robust in orthotopic xenografts. To determine whether the gene expression changes seen in the HPAF-II pancreatic cancer were generalizable to other Wnt-addicted cancers, we compared our data to our previously published data set of a Wnt-addicted jci.org Volume 128 Number 12 December 2018 (31). The promoters of genes in the most rapidly responding clusters (i.e., C9, C10, C20, C24, and C25; TI 50 < 20 hours) were rather significantly enriched for canonical E-box motifs, bound by transcription factors, including MYC, HEY1, CLOCK, and ID2 ( Figure 4A).…”
Section: Resultsmentioning
confidence: 99%
“…A number of zygotic Wnt-targets with enriched expression in the ventral mesoderm were components of BMP pathway including; bambi, bmp7, id2, msx1, smad7, szl, ventx1, and ventx3 (collectively known as the BMPsynexpression group) (von Bubnoff et al, 2005). Most of these genes are known to be directly activated by both Bmp4/Smad1 and zWnt8/Bcat (Itasaki and Hoppler, 2010;Stevens et al, 2017) but were upregulated, rather than downregulated, in Bcat-depleted embryos, likely due to the increase in BMP/zWnt8 signaling in ventralized embryos.…”
Section: B-catenin Directly Regulates the Endodermal Transcriptomementioning
confidence: 99%
“…Microinjection and embryo culture were preformed as previously described (Stevens et al, 2017) Antisense morpholino oligos (MO; GeneTools, LLC) were as follows: Synthetic mRNA for injections was generated using the Message Machine SP6 transcription kit (Thermo Fisher AM1340) using the following plasmids: pCS2+ human B-catenin S37A caBCAT) (Zorn et al, 1999); pcDNA6-V5-mouse Sox17 (mSox17) and pcDNA6-V5-Sox17…”
Section: Xenopus Embryo Manipulationsmentioning
confidence: 99%
“…Wnt/β-catenin signal transduction dysregulation can lead to an ARMs phenotype ( 31 ). Studies have revealed that this may be caused by abnormal BMP signaling, as BMP4 and BMP7 were abnormally increased in the β-catenin-induced ARM phenotype, and furthermore, knockout of the BMP receptor, BMPR1A, partially rescued the malformation ( 32 , 33 ). However, in the previous study, only the BMRP1A receptor was knocked out, whereas the other BMP receptor, BMPR2, was not altered.…”
Section: Discussionmentioning
confidence: 99%